Fundamental theory and cutting-edge applications of TENGs - Kang, Xilong; Li, Pengbo; Yurchenko, Daniil; Dai, Shuge; Wang, Junlei (Materials futures, 2025)
Since their birth in 2012, triboelectric nanogenerators (TENGs) have demonstrated astonishing development potential in the fields of energy, sensing, and advanced materials science. The capability of TENGs to convert high-entropy energy into electrical signals has led to technological breakthroughs in multiple domains. In the field of energy harvesting, TENGs have moved beyond conventional fluid energy harvesting, harvesting energy even from slow, low-frequency fluid motion. This has given them significant advantages in distributed energy scenarios. In the field of intelligent sensing, TENG-based sensors have achieved high sensitivity, driving advancements in the industrial Internet of Things and environmental monitoring. High-voltage output (tens of kilovolts) and contact electrification are two characteristics of TENGs. Based on these two characteristics, TENGs can be used to develop new high-voltage power sources and interface probe applications. This topical review introduces the working principles and theoretical foundations of TENGs and then presents four of their cutting-edge applications: fluid energy harvesting, self-adaptive sensors and systems, high-voltage power sources, and interface probes. Finally, the current challenges faced by TENGs in these fields are discussed, and some solutions are offered. This review not only provides a comprehensive overview of the latest applications of TENGs but also offers guidance for their future development.